Design of an Interleaver with Criteria to Improve the Performance of Turbo Codes in Short Block Lengths - Urrea-Onate, E; Kern-Molina, J; Lopez-Escobar, R (Springer, 2022)
This paper presents the design of an interleaver for short Parallel Turbo Codes (PTC) with short block lengths in the order of 64, 128, and 256 bits. In particular, the objective is to design an interleaver that generates decorrelation in the external input information to parallel recursive convolutional encoders, with sufficient data propagation to reduce the Bit Error Rate (BER). Experimental tests are designed and implemented −by numerical calculations− using the MatLab/Simulink software. The S-random interleaver, which applies circular displacement and a propagation constraint, is employed. An excellent reduction in BER is achieved for the three short block lengths, according to the quality indicator defined by the International Telecommunication Union (ITU). © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Turbo code; Interleaver; Short block; BER